New locations and parasitological findings for the invasive shrimp Palaemon macrodactylus in temperate southwestern Atlantic coastal waters - Martorelli, Sergio Roberto (2012)
This paper presents new records that considerably expand the geographical range of the invasive shrimp Palaemon macrodactylus in Argentina to include new estuarine areas on the Argentine south Atlantic coast: Bahía Samborombón, and the Bahía Blanca and Río Negro estuaries. The latter 2 locations are the southernmost reports for this species. The epibiotic barnacle Balanus amphitrite and a microphallid metacercaria Odhneria sp. are reported for the first time in P. macrodactylus. The prevalence of white spot syndrome virus (WSSV) was 10% in the Bahía Blanca estuary. Our results strongly suggest that WSSV is spreading in crustacean populations in the Argentine Sea and that P. macrodactylus plays a role in the ecology of parasite infections in this environment.